The Processes of Memorizing the Qur'an Program as An Optimization of Islamic Religious Education Learning in Shaping the Noble Morals of Students - Khaeruniah, Ade Een; Supiana, Supiana; Nursobah, Asep (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to analyze and describe: the paradigm, objectives, programs, processes, evaluations, supporting and inhibiting factors, and the impact of memorizing (tahfizh) the Qur'an tahfizh program as an optimization of Islamic Religious Education learning in shaping the noble character of students at SMP IT Qordova and SMP Al Amanah Bandung Regency. This research is qualitative research using phenomenological and ethnographic methods. Data collection techniques are carried out through interviews, observations, and literature. Data analysis is carried out by sorting out the data obtained and then collecting it for analysis and conclusions. The results of this study show that the process of the tahfizh Al-Qur'an program as an optimization of Islamic religious education learning in shaping the noble character of students in the two schools begins by strengthening the motivation and responsibility of students to learn by memorizing the Qur'an and is realized through the stages of planning, learning, using media, methods and learning administration. These findings highlight the Al-Quran tahfizh program as optimizing Islamic religious education learning in forming students' noble morals.